Assessment of Anti-fungal Drugs Utilization Pattern Among Patients Attending at Zewditu Memorial Hospital, Addis Ababa, Ethiopia, 2022 - Gebremariam, Samrawit Teame; Abafita, Robel Nasser; Fentaw, Dagmawi Mulugeta; Telila, Eden Kebede; Jeldu, Hosaena Alemayehu; Mulugeta, Betelhem Alemu; Woldie, Biruk Getachew; Baissa, Meron Tafa; Wollel, Mekdes Molla; Mandefro, Bethel Tadesse; Azale, Abrham Workineh; Tollosa, Tewodros Challa (British Journal of Healthcare and Medical Research, 2025)
Background: the inappropriate use of anti-fungal agents can cause adverse events, toxicity, unnecessary exposure and cost, and increased microbial resistance, which has important implications for morbidity and mortality. With a lack of adequate Information on how drugs are being prescribed and utilized, it is almost impossible to initiate a discussion on rational drug use or improvement on prescription habits and developing practical guidelines. Drug utilization might not necessarily provide answers on its own, but it contributes to rational drug use. Objective: To Assess anti-fungal agent utilization patterns among patients attending Zewditu Memorial Hospital, Addis Ababa, Ethiopia, 2022. Methodology: A Retrospective Cross-sectional study design was used. Data regarding patient characteristics, medications, diagnosis, dose and type of anti-fungal agent used were collected using data abstraction forms by reviewing the patient's medical card and medication charts. The data was entered into the SPSS 21 version for analysis. The analyzed data was interpreted and presented in charts, graphs and tables. Results: 124 anti-fungal agents were prescribed to 75 patients. Female patients received (n=66, 53.23%) of these prescriptions, and Male patients received (n=58, 46.77%).patients who were under 18 years old received (n=100, 80.6%), and patients who were 18 years old and above received (n=24, 19.3%).In this study, prescription of Fluconazole was(n=54, 44.4%) and Ketoconazole (n=55, 43.5%) while Clotrimazole was(n=9, 7.3%) and Terbinafine(n=6, 4.8%).the fungal infection of this patients were tinea capitis (n=48, 64%,) tinea unguium (n=13, 17.3%),tinea corporis(n=6, 8%)tinea pedis(n=7, 9.3%) tinea barbea (n=1, 1.3%). Conclusion: This study finding shows that Fluconazole was the most common anti-fungal drug prescribed orally, similar to elsewhere. However, oral Fluconazole was closely followed by Ketoconazole, which was the most frequently prescribed drug topically. This differed from other studies, meaning Clotrimazole was the most prescribed drug topically anti-fungal in different countries. Lastly, most studies support that Combination therapy of antifungals was more likely than Monotherapy.